Ästhetische Praxis: Texte zur Musik - Koenig, Gottfried Michael 1926-2021; Frobenius, Wolf 1940-2011; Konrad, Sigrid; Pfau, Roger; Fricke, Stefan (Saarbrücken Pfau, 1991)
"Gottfried Michael Koenig's aesthetic vanishing point is the complete understanding of all elements of a musical work, from the large-scale form to the individual vibration, resulting in continuous variability and infinite malleability of sound. All his writings revolve around it. Regardless of whether they are diary entries, commentaries on works, lectures, interviews, radio features or analyses of other people's works: the leading composer of electronic and programmed music, born in 1926, is always concerned with reassuring, explaining, expanding and conveying the interest, already evident in his earliest essays, in shaping the ungrasped dimensions of music, which are still beyond aesthetic mastery and merely conventionally given, at the level of what can already be anticipated in the compositional imagination." (Bernhard Uske, Positionen 19, May 1994)"There is no doubt that Koenig's writings are of central importance for our epoch, and their reading will soon be considered indispensable for all those who deal with the music of the recent past" (Till A. Körber, Musik & Ästhetik 6/1998) (Translated with DeepL.com)
Bd. 1. 1954-1961 -- Bd. 2. 1962-1967 -- Bd. 3. 1968-1991 -- Bd. 4. Supplement I (-- Bd. 5. Supplement II -- Bd. 6. Supplement III)
Includes bibliographical references and indexes.
Keywords: 20th Century (1901-2000); Music philosophy and esthetics; Music history; Music history